Evaluation of Salmonella Typhimurium Lacking fruR, ssrAB, or hfq as a Prophylactic Vaccine against Salmonella Lethal Infection - Park, Soyeon; Jung, Bogyo; Kim, Eunsuk; Yoon, Hyunjin; Hahn, Tae Wook (Vaccines, 2022)
Non-typhoidal Salmonella (NTS) is one of the primary causes of foodborne gastroenteritis; occasionally, it causes invasive infection in humans. Because of its broad host range, covering diverse livestock species, foods of animal origin pose a critical threat of NTS contamination. However, there is currently no licensed vaccine against NTS infection. FruR, also known as Cra (catabolite repressor/activator), was initially identified as the transcriptional repressor of the fructose (fru) operon, and then found to activate or repress the transcription of many different genes associated with carbon and energy metabolism. In view of its role as a global regulator, we constructed a live attenuated vaccine candidate, ΔfruR, and evaluated its prophylactic effect against NTS infection in mice. A Salmonella Typhimurium mutant strain lacking fruR was defective in survival inside macrophages and exhibited attenuated virulence in infected mice. Immunization with the ΔfruR mutant stimulated the production of antibodies, including the IgG, IgM, and IgG subclasses, and afforded a protection of 100% to mice against the challenge of lethal infection with a virulent Salmonella strain. The prophylactic effect obtained after ΔfruR immunization was also validated by the absence of signs of hepatosplenomegaly, as these mice had comparable liver and spleen weights in comparison with healthy mice. These results suggest that the ΔfruR mutant strain can be further exploited as a promising vaccine candidate against Salmonella lethal infection.
Keywords: cra; fruR; Salmonella infection; Salmonella vaccine